Pengaruh Kualitas Kehidupan Kerja dan Teamwork terhadap Kinerja Karyawan yang Dimoderasi Efektivitas Komunikasi - Muhammad Fauzan Azhmy; Tri Nur Ningsih (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2022)
From the initial research that researchers do, the phenomenon at the office of PT. Jiwasraya Cabang Medan, among others, placement of employees who have not been in accordance with the demands of office and educational background, so as not to meet the capacity capability as appropriate. The need for competent employees in accordance with the position of his position that has not sufficient cause the consequences of a less responsible attitude towards his work, the motivation for achievement to be lost, not enthusiasm work and feeling saturated. Such trends can occur in PT. Jiwasraya Cabang Medan, all of this stems from the mismatch of employee position placement with an existing workload that the interest or job satisfaction of employees decreased, while in terms of facilities and infrastructure and has been very supportive of employees in completing their work. The purpose of this study was to determine the effect of work placement, workload, and organizational culture on work motivation at PT. Jiwasraya Cabang Medan. The number of samples in this study amounted to 79 people using the curated sample technique. The analysis technique used is multiple linear regression. The results showed that simultaneously work placement variables, workload and organizational culture have a significant effect on employee work motivation. Job placement has no significant effect on employee work motivation, workload and organizational culture have an effect on employee work motivation